Are external accounts sustainable in Portugal? - Silva, Jorge (2018)
This study assesses the sustainability of the Portuguese external accounts during the period 1999-2014 and the role of the public sector. There was evidence of higher import content of the non-construction investment and private investment. Therefore, the high import content of the non-construction investment was an additional challenge because its increase did not create a strong positive multiplier effect on the Portuguese economy. Exports in volume were determined by the economic growth rate of the euro area, the share of the Portuguese nominal exports in the total exports of the euro area, unit labour costs of the private sector due to the compensation of employees and real productivity, the exchange rate and the terms of trade. There was no evidence of twin deficits. Additionally, there was a negative correlation between the internal and the external balance. Furthermore, we analysed the determinants of the liabilities related to the international investment position, decomposing the external funding and identifying their determinants.